Analisis Finansial Pendapatan Peternak Plasma Broiler Open House System PT X di Kabupaten Kediri - Niswatin Hasanah (Jurnal Ilmu Peternakan Terapan, 2018)
The study aimed to determine the production costs, revenue, earning, farming efisiency in terms of financial aspects. The farm efficiency can be obtained although R/C ratio, and BEP price during 6 production period of 30 plasma according to 3 scale enterprises. Birds stratum divided into stratum I (3.000â€“12.000 birds, n= 16), stratum II (12.001-21.000, n= 11), stratum III (21.001-30.000 birds, n= 3). The results indicated that the highest profit was strata III period 2 (Rp2,217.00/kg of live weight), the production cost was Rp14,700.00/kg of live weight (influenced by feed factor 75.7% and DOC 22.3%) and the revenue was Rp17,580.00 (consisted of affected by 98.8% broiler sales and bonus 0,57%) to produce 1 kilogram of live weight of broiler. In strata III period 2 the most efficient based on BEP price reached Rp15,252.00/kg broiler live weight and aspect R/C ratio was 1.17.Â